Motivasi Sebagai Variabel Mediasi Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan - Ni Luh Gede Putu Purnawati; Anak Agung Dwi Widyani; Kadek Dian Putri Anjaya (Jurnal Ilmiah Satyagraha, 2022)
This study aims to determine the effect of organizational culture onperformance and to determine the role of motivation in mediating it. The researchsample consisted of 42 people who were taken using the census method from allemployees. The collected data were analyzed using SmartPLS.From the analysis obtained: 1) Organizational culture has a positive andsignificant influence on motivation. The results of this study indicate that thebetter the organizational culture can increase motivation. 2) Organizational culturehas a positive and significant influence on employee performance. The results ofthis study mean that the better the implementation of organizational culture willbe able to improve employee performance. 3) Motivation has a positive andsignificant effect on employee performance. The results of this study mean thatincreased motivation can improve employee performance. 4) Motivation is able tomediate the influence of organizational culture on employee performance. Thisgives an indication that motivation strengthens the influence of organizationalculture on employee performance at PT. Prudential Life Assurance, PatimuraDenpasar Branch.